A Survey of Approaches for Sign Language Recognition System - N. , Kaushik; Rahul, Vaidya; K. , Senthil Kumar (International Journal of Psychosocial Rehabilitation, 2020)
Sign language is a form of communication for the deaf and dumb community with the rest of the world. But most of the people do not know or understand the sign language of these people which makes it very difficult for them to communicate with the rest of the world. The sign language recognition can have different level of success when it is based on different image processing techniques. There are a large number of sign languages which differ according to regions like the Indian Sign Language, Taiwanese Sign Language etc. The sign language can be represented as text by making use of Convolutional Neural Networks, Support Vector machines and other methods.